TNF‐α mediates the induction of nitric oxide synthase in macrophages but not in neutrophils in experimental cutaneous leishmaniasis - Simone Gonçalves Fonseca; Pedro Roosevelt Torres Romão; Florêncio Figueiredo; Ruth Helena de Morais; Hermenio Lima; Sérgio H. Ferreira; Fernando Q. Cunha (2003)
Abstract Leishmania major infection in C57BL/6 mice is controlled by the activation of a Th1 response and nitric oxide (NO) production by macrophages. TNF‐α is considered one of the most important cytokines involved in this response. In the present study, we investigated the expression of nitric oxide synthase (iNOS) in the inflammatory cells present in the lesion and draining lymph nodes, and the cytokine production by lymph node cells in animals treated with anti‐TNF‐α. Our results demonstrated that mice treated with anti‐TNF‐α presented an increase in the number of parasites and the size of lesion, but they were able to control the infection. The increase in the lesion size correlated to the reduction of iNOS activity in the draining lymph nodes. Furthermore, the anti‐TNF‐α treatment also reduced the expression of iNOS in the macrophages, but did not affect the iNOS expression in the neutrophils. The anti‐TNF‐α mAb did not reduce the iNOS expression in IFN‐γ‐stimulated L. major infected neutrophils in vitro . Anti‐TNF‐α mAb treatment caused an increase in the production of IFN‐γ and IL‐10 by the lymph node cells from infected mice. Consequently, these results suggest that neutrophils do not respond to anti‐TNF‐α treatment and might be a source of NO to control L. major infection under these experimental conditions.